"I'm Not a Juvenile Delinquent": 1950s Rock'n'roll, Youth under Threat, and Good Citizenship in US Exploitation Cinema 1956–59. (15th May 2017) - Baker, David; Istvandity, Lauren
Abstract : The jukebox musical, a format of youth-oriented film based on performances of well known rock'n'roll artists, found considerable popularity in the late 1950s. In response to the commercial rise of youth-oriented popular music, jukebox musicals modulated the ways in which they portrayed rock'n'roll and its perceived social and moral effects on the young. This article concentrates on the most intense period of this activity, 1956–59, in which we describe filmic narratives as moving through classic, transitional and secure phases. Select films of US production companies are thematically analysed to reveal the evolution of rock'n'roll narratives using two key tropes for rock being a threat to youth wellbeing as well as a catalyst for good citizenship. This article demonstrates the tension between a developing youth music market, social values and filmic representation during this significant period of popular music history.